PENGEMBANGAN SUMBER DAYA MANUSIA ORGANISASI LEMBAGA PEMBERDAYAAN MASYARAKAT DALAM PEMBERDAYAAN PETANI MISKIN - Kahar Saleh; Abdul Mahsyar; Anwar Parawangi; Fatmawati Fatmawati (JPPM: Journal of Public Policy and Management, 2021)
This research is motivated by the development of Community Empowerment Institution resources which function as a forum for village communities to plan development and foster village communities. The research method aims to describe the development of local government capacity in empowering farming communities in Bulukumba Regency. In this case, this research uses descriptive type to describe the observed behavior. The research focus is based on the grinddle theory which looks at resources, organizational strengthening, and institutional reform. Data collection includes in-depth interviews, observations and documentation. In his research for about 3 months, the data analysis technique in this study was carried out qualitatively. The results of the study indicate that in carrying out its functions, institutional management is not optimal in developing community empowerment of farmers. Flexible and adaptive institutional development in order to optimize the achievement of national development in a synergistic manner between the central government, regional governments, and institutions. and the factors that hinder Community Empowerment Institutions in carrying out their functions are due to the absence of innovation in management so that there are limited collaboration networks or partnerships with other institutions.